2016
DOI: 10.1097/md.0000000000004366
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal comparison of quality of life in patients undergoing laparoscopic Toupet fundoplication versus magnetic sphincter augmentation

Abstract: Only a minority of patients with gastro-esophageal reflux disease (GERD) are offered a surgical option. This is mostly due to the fear of potential side effects, the variable success rate, and the extreme alteration of gastric anatomy with the current gold standard, the laparoscopic Nissen fundoplication. It has been reported that laparoscopic Toupet fundoplication (LTF) and laparoscopic sphincter augmentation using a magnetic device (LINX) can treat reflux more physiologically and with a lower incidence of si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 23 publications
1
27
0
2
Order By: Relevance
“…15 Durability has been assessed out to 5 years, and there has been little deterioration in success over time, with 85% or more of patients experiencing relief of typical GERD symptoms without requiring daily acidsuppressive medication. 18,19,38 The success of MSA in controlling regurgitation seen in this study is in line with previous MSA studies. 19 Surgical treatment for refractory GERD often is overlooked or discounted for a variety of reasons: concern about durability, side effects, and the presumption that refractory GERD symptoms are not in fact because of GERD.…”
Section: Discussionsupporting
confidence: 91%
“…15 Durability has been assessed out to 5 years, and there has been little deterioration in success over time, with 85% or more of patients experiencing relief of typical GERD symptoms without requiring daily acidsuppressive medication. 18,19,38 The success of MSA in controlling regurgitation seen in this study is in line with previous MSA studies. 19 Surgical treatment for refractory GERD often is overlooked or discounted for a variety of reasons: concern about durability, side effects, and the presumption that refractory GERD symptoms are not in fact because of GERD.…”
Section: Discussionsupporting
confidence: 91%
“…Five, including the RCT, reported differences in patient baseline demographics, including hernia size, obesity, age, DeMeester score and disease severity, which were not accounted for in analyses. Although four reported ‘matched’ controls, there were differences in demographics in three.…”
Section: Resultsmentioning
confidence: 99%
“…). A total of 39 full‐text papers, published between 2008 and 2019, were finally included. The 39 articles consisted of one RCT, five comparative cohort studies (2 prospective and 3 retrospective), three comparative case–control studies, 25 case series (14 prospective, 11 retrospective) and five case reports ( Fig .…”
Section: Resultsmentioning
confidence: 99%
“…Earlier concerns regarding postoperative dysphagia following Nissen fundoplication in conventional manometry‐based IEM have been refuted by four small randomized controlled trials demonstrating similar overall outcomes after a partial (Toupet or Dor) fundoplication. Ineffective esophageal motility is a relative contraindication for magnetic sphincter augmentation (MSA), as peristalsis provides propulsive force to distend the magnetic band of the MSA device . Statistically significant augmentation of proportions of intact peristaltic sequences and of distal esophageal amplitudes has been reported in IEM following fundoplication .…”
Section: Discussionmentioning
confidence: 99%
“…Ineffective esophageal motility is a relative contraindication for magnetic sphincter augmentation (MSA), as peristalsis provides propulsive force to distend the magnetic band of the MSA device. 112,113 Statistically significant augmentation of proportions of intact peristaltic sequences and of distal esophageal amplitudes has been reported in IEM following fundoplication. 104,105,114 In contrast, Booth et al and Mello et al found that while some IEM patients exhibited improvement, others had a decline in peristalsis, and some with normal peristalsis pre-operatively developed IEM postoperatively.…”
Section: Iem and Antireflux Surgerymentioning
confidence: 99%